Assessing the Impact of Household Socioeconomic Factors on Clean and Healthy Living Behaviors with Binary Logistic Regression: A Study in Probolinggo Regency - Nafis, Moch Abdillah Nafis; Destri Susilaningrum; Brodjol Ulama; Dwi Endah Kusrini (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
CHLB is a measure of livability in society. A high CHLB indicates a society that lives well. However, there is a problem in the probolinggo district that needs more effective public health interventions because of the area's fast population growth and a noticeable increase in infectious diseases. The adoption of Clean and Healthy Living Behaviors (CHLB) by Probolinggo district is the main focus of this study to find out who is still living below the applicable eligibility standards. In order to minimize the spread of infectious diseases and enhance general public health in Probolinggo Regency, policymakers and healthcare professionals are anticipated to find great value in the study's findings. It also examines the use of binary logistic regression with binary transformation all categorical variables as a supplemental technique for managing complex data relationships and enhancing predictive accuracy. In addition to addressing the pressing issues in public health, this study advances our knowledge of the socioeconomic factors that influence health in rural Indonesia.